ANALYSIS OF USAGE ACCEPTANCE OF MOBILE BANKING APPLICATIONS TECHNOLOGY ACCEPTANCE MODEL (TAM) APPROACH: English - Sawa, Hira; Prayoga, Rangga; Sopian, Najwar (Educational Researcher Journal, 2024)
This research aims to evaluate the factors that influence the behavior of the experience of using the livin application from Bank Mandiri. The approach used is the Technology Acceptance Model (TAM) model developed by Davis in 1989, with a focus on benefits and ease of use, as well as the addition of two external variables, namely security and compatibility. This model was tested empirically using survey data from Livin Application Users from Bank Mandiri. From the results of data analysis obtained during the research, the results show that the use of the Livin application from Bank Mandiri has fulfilled two main aspects in the Technology Acceptance Model (TAM) theory. The Livin application is considered useful for assisting work at Bank Mandiri in the customer service process. From this research it is also known that the use of the Livin Application is not optimal and can still be improved by increasing the benefits of the Liven Application. The Livin application is also easy software, both in terms of installation and modification and easy to use, but efforts are still needed to improve the user's ability to utilize the Livin application.